Study of Stresses Induced in Axisymmetric Buried thin Orthotropic Empty Cylindrical Shell Due to Shear-wave Loading - Singh V.P.; Dwivedi J.P.; Lal R.K.; Kumar P. (My University, 2025)
Axisymmetric dynamic response and the stresses induced in an empty buried pipe due to an incident shear wave under different soil conditions is the subject of this investigation. In this work the shell is assumed perfectly bonded to the surrounding medium of infinite extent. The pipeline has been modelled as an infinitely long circular cylindrical shell buried in homogeneous, isotropic and elastic medium of infinite extent. For perfect bonding between soil and pipe, the stiffness and damping properties of soil are neglected. Results have been obtained for hard (rocky), medium hard and very soft (sandy) soil conditions surrounding the shell. The stress variations of pipe due to changes in properties of surrounding medium have been carefully studied of different angles of wave incidence. The different kinds of soils from soft and sandy to hard and rocky conditions have been taken into account. It is realised that the orthotropic parameters have a significant influence on the stresses (axial and hoop) depending on the soil conditions and the angle of incidence. © 2015 Elsevier Ltd.